2020
DOI: 10.1038/s41598-020-74911-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation potential of selenium nanoparticles and riboflavin against arsenic and elevated temperature stress in Pangasianodon hypophthalmus

Abstract: Climate change impact has disturbed the rainfall pattern worsening the problems of water availability in the aquatic ecosystem of India and other parts of the world. Arsenic pollution, mainly through excessive use of groundwater and other anthropogenic activities, is aggravating in many parts of the world, particularly in South Asia. We evaluated the efficacy of selenium nanoparticles (Se-NPs) and riboflavin (RF) to ameliorate the adverse impacts of elevated temperature and arsenic pollution on growth, anti-ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 96 publications
(105 reference statements)
0
19
0
Order By: Relevance
“…In a feeding trial that lasted for 70 days, Khan et al [ 48 ] and Khan et al [ 58 ] reported that Mahseer fish displayed increased growth performance. Kumar et al [ 59 ] and Kumar et al [ 60 ] stated that Pangasinodon hypophthalmus treated with Se nanoparticles at 1–2 mg/kg had enhanced growth performance. Further, rainbow trout ( Oncorhynchus mykiss ) fed dietary Se nanoparticles at 2 mg/kg for 60 days had enhanced growth performance and feed utilization [ 61 ].…”
Section: The Role Of Selenium Nanoparticles On the Growth Performancementioning
confidence: 99%
See 2 more Smart Citations
“…In a feeding trial that lasted for 70 days, Khan et al [ 48 ] and Khan et al [ 58 ] reported that Mahseer fish displayed increased growth performance. Kumar et al [ 59 ] and Kumar et al [ 60 ] stated that Pangasinodon hypophthalmus treated with Se nanoparticles at 1–2 mg/kg had enhanced growth performance. Further, rainbow trout ( Oncorhynchus mykiss ) fed dietary Se nanoparticles at 2 mg/kg for 60 days had enhanced growth performance and feed utilization [ 61 ].…”
Section: The Role Of Selenium Nanoparticles On the Growth Performancementioning
confidence: 99%
“…Concurrently, Khan et al [ 48 ] and Khan et al [ 58 ] reported that Mahseer fish fed dietary Se nanoparticles (0.68 mg/kg) had increased red blood cell count, hemoglobin level, hematocrit values, and lysozyme activity. Kumar et al [ 60 ] reported that P. hypophthalmus fed dietary Se nanoparticles (0.5 mg/kg) had increased acetylcholine esterase, NBT, total immunoglobulin, myeloperoxidase, globulin, and reduced serum cortisol, lipid peroxidation, and blood glucose. Nazer et al [ 61 ] reported that rainbow trout fed dietary Se nanoparticles (2 mg/kg) had increased red blood cells, hemoglobin, and hematocrit.…”
Section: Effect Of Selenium Nanoparticles On the Immunological Biochemical And Hematological Parameters Of Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies evaluated the protective effect of riboflavin (and selenium nanoparticles) on reducing the adverse effects of iAs in Pangasianodon hypophthalmus reared in the presence of iAs and high temperature [19,20] (Table 3).…”
Section: Vitamin B 2 With Seleniummentioning
confidence: 99%
“…In the studies involving Pangasianodon, only tAs bioaccumulation in various organs was analyzed. Vitamin B 2 supplementation caused a reduction in tAs concentration in the liver, gills, brain, kidneys, and muscles [19,20].…”
Section: Vitamin B 2 With Selenium-ias Metabolismmentioning
confidence: 99%